Toll-like receptor 7 involves the injury in acute kidney ischemia/reperfusion of STZ-induced diabetic rats - Yayi,Huang (2016)
ABSTRACT PURPOSE: To determine whether Toll-like receptor 7 (TLR7) is the potential targets of prevention or progression in the renal ischemia/reperfusion (I/R) injury of STZ-induced diabetic rats. METHODS: Thirty six Sprague-Dawley rats were randomly arranged to the nondiabetic (ND) or diabetic group (DM), with each group further divided into sham (no I/R injury), I/R (ischemia-reperfusion) and CD (given by Chloroquine) group. Preoperatively, Chloroquine (40 mg/kg, intraperitoneal injection.) was administrated 6 days for treatment group. I/R animals were subjected to 25 min of bilateral renal ischemia. Renal function, histology, apoptosis, cytokines, expression of TLR7, MyD88 and NF-κB were detected. RESULTS: The serum levels of blood urea nitrogen, creatinine, IL-6 and TNF-α, apoptotic tubular epithelial cells, expression of TLR7, MyD88 and NF-κB were significantly increased in DM+I/R group, compared with ND+I/R group (p<0.05). All these changes were further improved by TLR7 inhibition Chloroquine except Paller scores (p<0.05). CONCLUSION: Toll-like receptor 7 inhibition attenuates the acute renal ischemia/reperfusion injury of STZ-induced diabetic in SD rats.